Evaluation of potential role Phaleria macrocarpa and Gynura procumbens in the prevention of azoxymethane-induced aberrant crypt foci in rat colon / Abdrabuh Naji Shwter - Abdrabuh Naji, Hussein Shwter (2017)
Phaleria macrocarpa and Gynura procumbens extracts are traditionally used to treat different diseases in Malaysia and Indonesia. The aim of this research is to evaluate the chemopreventive effects of ethanol extracts of P. macrocarpa and G. procumbens against azoxymethane-induced (AOM) aberrant crypt foci (ACF) in male Sprague Dawley rats. Our acute toxicity studies revealed no hepatotoxic and nephrotoxic effects. In vitro, both plant extracts exhibited high antioxidant activities which were due to the presence of high phenol and flavonoid content. Moreover, the results from the MTT assay showed antiproliferative activity of both plant extracts against colon cancer cell line HT29. Gross examination of rats treated with the plant extracts showed a significant reduction in the number of ACF. Histological evidence showed remarkably elongated glands with stratified nuclei, and depletion of mucin in the colon of AOM group compared to the plant extract-treated group. Immunohistochemical staining showed proliferating nuclear cell antigen (PCNA)-positive cells were significantly higher in the AOM group compared to the plant extract-treated rats. In colon tissue homogenate, glutathione S-transfarease (GST) and superoxide dismutase (SOD) activities were significantly higher whilst malondialdehyde (MDA) level was significantly lower in extract-fed rats compared to AOM groups. RT-PCR showed that P. macrocarpa and G. procumbens altered the expression of apoptosis-related genes; the anti-apoptotic protein Bcl-2 was downregulated whereas the pro-apoptotic protein Bax was upregulated. Furthermore, the active constituents isolated from both plants were identified. Based on the results of this study, P. macrocarpa and G. procumbens ethanol extracts were nontoxic after oral administration. The chemopreventive potential of these plant extracts was demonstrated by reductions in the numbers of ACFs which could be attributed to their antioxidant properties and down-regulation of PCNA-promoting proteins in cancer cells. In addition, gene expression analyses revealed that both plant extracts activated apoptosis.